EFFECT OF FLY ASH AND ALUMINIUM POWDER ON STRENGTH PROPERTIES OF CONCRETE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Light weight concrete (LWC) shall be stated as a type of concrete which includes as a rising agent and it increases the quantity of mixture despite the fact that lowering the dead weight. When compare to normal concrete its weight is less and dry density lesser than 2000kg/m3. The major specialties of the LWC are the less density and low thermal conductivity. The objective of this investigation is to develop the most economical light weight concrete for building with satisfactory amount of compressive strength. Fly ash replacement is fixed to as 5%, 10%and 15 % of the cement in the mixture. The percentage addition of aluminum powder is limited to three categories that are 0, 0.5 and 1 to the light weight concrete mixture. At 15 % replacement of fly ash, the tested concrete block have maximum compressive strength and split tensile strength. It is found that, after adding up of aluminum powder, there is a gradual decrease in compressive strength and split tensile strength. Combination of fly Ash (15%) and Aluminum powder (0.25%) gives higher compressive strength and split tensile strength.